The Role of Micro, Small, and Medium Enterprises (MSMEs) and the Impact of Plastic Waste Use by Tofu Factories on Islamic Business Ethics in Krian District, Sidoarjo - Nurhabits Safitri; Abdur Rohman (Penerbit Hellow Pustaka, 2026)
This research examines how Micro, Small, and Medium Enterprises (MSMEs) play a role in the local economy and the impact of using plastic waste from tofu factories on Islamic business ethics in Krian-Sidoarjo District. Small and medium enterprises (MSMEs) play an important role in creating jobs and driving economic growth, but unsustainable production practices, such as the use of plastic waste, present ethical challenges that need to be reviewed from an Islamic perspective. Islamic business ethics emphasize the principles of sustainability, justice, and the common good, which should guide business actors, including in waste management. This research identifies the motivations, practices, and impacts of plastic waste usage by tofu factories, as well as how this usage can be aligned with Islamic business principles. The research employs a qualitative approach. This research uses a qualitative approach. It is hoped that the research results will assist stakeholders in making plans that support the sustainability of MSMEs and meet Islamic business ethics.